The role of urbanization in soil and groundwater contamination by heavy metals and pathogenic bacteria: A case study from Oman. Issue 5 (May 2019) - Shaharoona, Baby; Al-Ismaily, Said; Al-Mayahi, Ahmed; Al-Harrasi, Nadhira; Al-Kindi, Ruqaiya; Al-Sulaimi, Abdullah; Al-Busaidi, Hamad; Al-Abri, Mohammed
Abstract: This study assessed the perception of urban residents of A'Seeb city, Oman, about the impact of their activities on environment. A sociological survey using questionnaire was used to know the residents' perceptions about urban gardening, municipal-waste disposal, and soil and water contamination. Viable pathogenic bacteria, water soluble metals, basic cations, salinity, and texture were quantified and identified in soil and groundwater in proximity of urban gardens and municipal-waste disposal sites. The majority of surveyed residents are not paying attention to the negative consequences of their activities on soil and environment. Although the measured heavy metals concentrations in some of the contaminated sites were significant but still below the international standards. Fecal contaminants reported in in some samples from gardens, garbage-disposal sites and groundwater. Human pathogens belonging to risk group-2 including Klebsiella pneumonia, Shigella spp and E. Coil were identified. More socio-environmental studies required to correlate the behavior of urban residents and pollution and to delineate the sources of the detected pathogenic bacteria. Our results set a foundation for future studies on urban soils and associated residence behaviors and practices in Oman and the neighboring Gulf countries.